Harry Potter da magia à ciência: uma sequência didática sobre a história da tabela periódica por meio de história em quadrinhos. - CONCEIÇÃO, Joseane Cunha da (2024)
The research in question sought to develop and evaluate a didactic sequence that involved the content of the periodic table, from a historical perspective, approaching the theme using the Harry Potter narrative and the philosopher's stone as a means of contextualization and an authorial comic book as teaching material, in order to assess the level of motivation and involvement of 9th grade students in elementary school for learning chemistry. For this, 3 classes on the subject were planned, developed and applied in a public-school class, involving scenes from the film, authorial comics and discussions on the historical process of the construction of the periodic table. Faced with the construction of an authorial didactic material, the step-by-step process for the development of a comic book to be used in the classroom is described. Data collection was carried out through audio recordings, for the extraction of dialogues, intriguing questions from the teacher, questions from the students, application of questionnaires, in order to extract opinions about the application of the didactic sequence and the construction of a story in comics made by the students with a theme chosen by the teacher, in order to observe the student's understanding of the subject covered. During the analysis of the students' responses both in the questionnaires and in the dialogues, an enthusiasm and curiosity for the subject was noted. In general, the research showed positive results regarding the methods used in the didactic sequence, implies that using historical facts and approaching them in an attractive way through films and comic books, to show the human construct about science, it can help in the teaching and learning process in chemistry, arousing curiosity and provoking motivation.